1990
DOI: 10.1063/1.346524
|View full text |Cite
|
Sign up to set email alerts
|

A new portrayal of electron and hole traps in amorphous silicon nitride

Abstract: Trap centers in amorphous silicon nitride (a-SiNx) have been considered to be amphoteric. We found two signals of Si3 3/4 Si0 and N3 3/4 Si0 (Si dangling bonds with an unpaired electron) by an electron-spin-resonance method, and estimated the hole trap density to be larger than the electron trap density by about one decade, using the nonvolatile memory devices. As a result, we propose a new portrayal in which electron/hole traps are at the interface between Si clusters and a-SiNx bulk, and hole traps are at ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…1 These traps have been attributed to different types of silicon dangling bonds, termed K-center defects, based on electron spin resonance (ESR) measurements, [1][2][3][4] and electronic structure calculations of some native defects. [5][6][7][8] However, a comprehensive characterization of the atomic and electronic structure of e − and h + traps in silicon nitride is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…1 These traps have been attributed to different types of silicon dangling bonds, termed K-center defects, based on electron spin resonance (ESR) measurements, [1][2][3][4] and electronic structure calculations of some native defects. [5][6][7][8] However, a comprehensive characterization of the atomic and electronic structure of e − and h + traps in silicon nitride is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the silicon dangling bonds can exchange electrons and the coulomb interaction at this distance is strong. However, experiments [4,19,20] showed that the electron trap density (N −1/3 and is about 60Å which much larger than that used in the ab initio DFT calculation conducted by Pacchioni and Erbetta [18]. At the distance estimated from the experimental trap density, the Coulomb interaction is too week to make the electron exchange between two N 3 Si· defects happening.…”
Section: (Received 30 January 2003)mentioning
confidence: 88%
“…In addition, if the distance between two defects is about 3.1Å, other mechanisms for the carrier localization are also possible. It was suggested that the electron and hole capturing could also occur at a neutral diamagnetic ≡ Si−Si ≡ defect [2,4,10,20,21]. The validity of these two models for Si 3 N 4 is still under discussion.…”
Section: (Received 30 January 2003)mentioning
confidence: 99%
“…Our works extends the model based on electron and hole trapping at the O 3 Si=Si O 3 defect in silica (see Fig. 1) proposed earlier (1,2,8) and predict the geometry, electronic structure and spectroscopic properties of doubly ionized and negatively charged oxygen vacancies in a-SiO 2 . We argue that the oxygen vacancies can be responsible for both the electron and hole trapping in silica.…”
Section: Ecs Transactions 19 (2) 3-17 (2009)mentioning
confidence: 93%